(untitled) (Quinto Sol, 2024)
This work reconstructs the emergence of youth supplements in national newspapers in the 1980s. On the one hand, the article produces a map of the appearance of these supplements from 1982 to 1988 and, based on these findings, analyzes the cultural and political significance of youth in the context of the so-called “transition to democracy”. On the other hand, the article focuses on the most read of these supplements, Si, which appeared every Friday with Clarín. Focusing on that supplement, the article shows the construction of the editorial project (journalists, financing, aesthetic relationships with underground fanzines); the central importance that rock had as an element that was conceived of as inseparable from youth identities as well as a platform for attracting a broader readership (especially avid to get information on the weekend agenda); and the transformations in the youth market. Likewise, the article follows the other themes and problems that the supplement associated with youth, including vocational orientation, sexual education, and politics.